The Influence of religious Moderation on Increasing Prosocial Attitudes and The Spirit of Nationalism in Generation Z - Mustikawan, Alfin; Ghozi, Ahmad; Wahyu Hidayat, Imam; Hidayati, Fina (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2024)
Gen Z is a tech-savvy generation with characteristics that have a high attachment to the social environment, especially their peers. Environmental influences, such as social media that can no longer be dammed, make Gen Z easily swayed by all the information obtained. Emotions that are still unstable, also make Gen Z unable to think logically and their behaviour is easily shaped by their social groups. An important foundation for Gen Z, especially for social skills, is the attitude of religious moderation. The religious moderation approach that Gen Z has, is able to act in the middle, respect others, and create harmony between groups and communities. The purpose of this study is to prove the implementation of the value of religious moderation through prosocial attitudes and the spirit of nationalism. This research is a quantitative approach, with a convenience sampling technique. Respondents in this study were 413 people, consisting of 55.9% men and 44.1% women. The instruments used were religious moderation scale for adolescents, Prosocial Tendencies Measure (PTM), and nationalism spirit scale. The analysis used was multiple regression test using t-test. The results showed that prosocial attitudes were able to predict β = 21.5%, and the spirit of nationalism β = 34.2% of Gen Z's religious moderation attitude. These results indicate that the behaviour of helping others, having empathy, respecting others, accepting cultural diversity in Indonesia and realising group and community harmony is an implementation of religious moderation attitudes in Gen Z. The approach of prosocial attitudes and the spirit of nationalism can be introduced and started early, so that the attitude of religious moderation can be the main foundation when children enter adulthood.